Study of anomalies associated with labiopalatine clefting - Pradipta Ray Choudhury; K L Talukdar; J Sarma; Prabahita Baruah (Wolters Kluwer Medknow Publications, 2012)
Background and aims: Cleft lip with or without cleft palate are the most common congenital malformations of the head and neck accounting for about 65% of all anomalies of this region. Approximately 70% of cleft cases are non-syndromic and occur as isolated condition, while remaining 30% cases are associated with systemic defects involving cardiovascular, musculoskeletal, genitourinary system and other structural anomalies. The purpose of this study is to assess the various anomalies associated with labiopalatine clefting. Materials and methods: Sixty four cases of cleft lip with or without cleft palate attending the OPD of Department of Plastic Surgery and Pediatric Surgery, Gauhati Medical College and Hospital, were studied. Among them three cases were found to be associated with other anomalies. Results: One case of cleft lip and palate presented with multiple anomalies like tongue tie, malformed external ear and micrognathia. Another one had acyanotic heart disease associated with cleft lip. A case of cleft lip and palate was also found to be associated with hydrocephalus. Conclusion: Proper knowledge and details of anomalies associated with orofacial cleft will help to provide necessary treatment and improve survival of these children.